2021
DOI: 10.3389/fbioe.2021.613787
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Materials for Soft Tissue Repair

Abstract: Over the past decades, age-related pathologies have increased abreast the aging population worldwide. The increased age of the population indicates that new tools, such as biomaterials/scaffolds for damaged tissues, which display high efficiency, effectively and in a limited period of time, for the regeneration of the body's tissue are needed. Indeed, scaffolds can be used as templates for three-dimensional tissue growth in order to promote the tissue healing stimulating the body's own regenerative mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 144 publications
(194 reference statements)
1
74
0
Order By: Relevance
“…Biomaterials provide the biological structure that supports MSC osteogenic differentiation [2,[11][12][13][14][15][16][17][18]. The addition of ions has been proved to enhance the osteogenic potential of scaffolds [19].…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials provide the biological structure that supports MSC osteogenic differentiation [2,[11][12][13][14][15][16][17][18]. The addition of ions has been proved to enhance the osteogenic potential of scaffolds [19].…”
Section: Introductionmentioning
confidence: 99%
“…The use of different biomaterials in periodontal regeneration has been studied for years. Several treatment options for periodontal disease include open flap debridement (OFD), biologically active regenerative materials, bone-replacement graft materials, scaling and root planning, and guided tissue regeneration with barrier membranes [87][88][89][90][91][92]. The combined use of barrier membranes and biomaterials was shown to be more effective than using OFD alone.…”
Section: Dental Therapymentioning
confidence: 99%
“…Exposure of musculoskeletal tissues to hypergravity may constitute a way of simulating (over)loading or, eventually, to be used as a measure to rescue cell phenotype after exposure to near-weightlessness conditions [103]. Effects of hypergravity (5,10,15, and 20 g) on the viability of hTDCs and expression of tendon-related genes were evaluated. It was found that the expression of scleraxis (Scx), tenascin (TNC), decorin (DCN), and III (COL3A1) was significantly increased by 4-, 5.4-, 6.4-, and 7-folds, respectively, at 15 g after 16 h. However, no difference was observed in the transcription level of tenomodulin (TNMD) and collagen type I (COL1A1) as compared to the control (Figure 8).…”
Section: Mechanical Stimulationmentioning
confidence: 99%
“…Several natural and synthetic polymers are currently in use to fabricate 3D scaffolds with enormous processing flexibility. Natural polymers like gelatin, chitosan, alginate, collage, and synthetic polymers, such as poly(lactic-co-glycolic acid), polylactide, polycaprolactone, polyurethane, and poly(glycerol sebacate), are common biomaterials used for tissue engineering [15]. Based on the wide range of materials available to date, the selective process plays a pivotal role, and it is influenced by several parameters like biodegradability, compatibility, severity of injury, and type of tendon tissue [16][17][18].…”
Section: Introductionmentioning
confidence: 99%